PEMERIKSAAN KESEHATAN SERTA PENGOBATAN GRATIS DI AKADEMI AKUNTANSI BANDUNG (A2B) - Terawati, Mira Teram; Rachman, Fatwa Rubiar; Suryati, Elis (Publika Citra Media, 2024)
Health is a state of complete physical, mental and social well-being and not simply free from disease or weakness. Through community service activities packaged in the 53rd Anniversary program of the Bandung Accounting Academy (A2B), A2B partnered with the Red Beret Corps Children (AKBM) and SMK Dharma Bhakti Indonesia (SMK DBI) to hold free medical check-up and treatment activities in the form of checking blood pressure, blood sugar, and uric acid as well as providing free consultations and medicines by doctors. It aims to monitor the health of the local community and early detect non-communicable diseases that may arise. This activity is expected to increase the awareness of the elderly regarding the importance of carrying out a healthy lifestyle to avoid disease.